(untitled) (Fiep Bulletin - online, 2013)
Analyze the level of balance among the regular elderlies and beginners in water aerobics of a project in Dourados/MS. Classify the level of the elderlies’ body balance who practice water aerobics for more than one year and the beginners of the related project according to a scale of Berg’s functional balance and compare the balance results obtained between the both groups. The sample was composed by thirty elderlies, being fifteen regulars of water aerobics for more than one year (control group) and fifteen elderlies beginners (experimental group), being twenty-seven women and three men, taking place in a Private Institution of Dourados/MS, where it works the Water Aerobics Project for elderlies for three years, three times a week, with duration of one hour, under orientation of the Clinic of Physiotherapy of the referred Institution. Through the research result showed in the pictures it was certified that the regular elderlies have low risk of fall (score between 41 to 56) representing 100% of the sample, while the elderlies who started obtained 60% of low risk of fall and 40% of medium risk of fall (score between 21 to 40) and no group presented a high risk of fall (0 to 20). Through this study it can be concluded that the elderlies who practice water aerobics regularly have better balance against the beginners, reducing, this way, the possibility of fall, what suggests that the regular and orientated practice of physical activity offers more stability for the body.